Evaluation of reproductive performance of indigenous and crossbred cattle in kerala: A field level study - K. Anilkumar; G. Radhika; P. Divya; C. B. Bimal; T.V. Aravindakshan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A survey was conducted among the small holder dairy farmers in 80 Panchayaths of 14 districts in Kerala in order to evaluate the reproductive performance of crossbred cattle population in Kerala at field level. Analysis of the data showed that the herd size of cattle in Kerala was around 3 per house during the period of 2012 and 2013. Three fertility traits, age at first calving (AFC), calving interval (CI) and number of services per conception (NSC) were studied in detail and the averages of these traits were 1093 ± 10.52 days, 551 ± 48 days and 2.02 ± 0.01 services per conception, respectively. Fixed model analysis was carried out to see the effect of some of the major factors leading to variation in AFC, CI and NSC and found that there was significant difference in reproductive performances among different genetic groups. AFC and NSC of crossbred Holstein Friesian cows and CI of Sunandini cows were lower compared to other genetic groups. Other factors significantly influencing AFC were period of birth and season of birth. Apart from genetic groups, number of services per conception was influenced by type of semen used and also the level of peak milk production.